2005
DOI: 10.1002/jmri.20427
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of posture on intracranial physiology in humans by MRI flow studies

Abstract: Purpose:To quantify the effect of posture on intracranial physiology in humans by MRI, and demonstrate the relationship between intracranial compliance (ICC) and pressure (ICP), and the pulsatility of blood and CSF flows. Materials and Methods:Ten healthy volunteers (29 Ϯ 7 years old) were scanned in the supine and sitting positions using a vertical gap MRI scanner. Pulsatile blood and CSF flows into and out from the brain were visualized and quantified using time-of-flight (TOF) and cine phase-contrast techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
189
2
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 180 publications
(217 citation statements)
references
References 13 publications
21
189
2
5
Order By: Relevance
“…For example, moving from the upright to the supine position alters venous outflow, with redirection of venous return from the vertebral venous plexuses to the internal jugular veins; decreases intracranial compliance; and increases intracranial pressure. 10 In this study, we found the following: 1) no significant group differences in GM, WM, CSF, or ventricular volumes between pre-and post-bed rest; 2) shift of the center of mass of the brain upward and posterior rotation of the brain relative to the skull; 3) significant correlation between posterior brain rotation and changes in ventricular volume; and 4) significant increases in brain tissue density in brain regions at the vertex, including the central frontoparietal lobes, with associated contraction of the adjacent extra-axial CSF spaces and significant decreases in tissue density in areas along the base of the brain, including the orbitofrontal cortex, with expansion of the basal extra-axial CSF spaces. We hypothesize that these unique structural alterations occurring during bed rest and possibly during spaceflight due to altered gravity gradients may provide explanations for the findings of the VIIP syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…For example, moving from the upright to the supine position alters venous outflow, with redirection of venous return from the vertebral venous plexuses to the internal jugular veins; decreases intracranial compliance; and increases intracranial pressure. 10 In this study, we found the following: 1) no significant group differences in GM, WM, CSF, or ventricular volumes between pre-and post-bed rest; 2) shift of the center of mass of the brain upward and posterior rotation of the brain relative to the skull; 3) significant correlation between posterior brain rotation and changes in ventricular volume; and 4) significant increases in brain tissue density in brain regions at the vertex, including the central frontoparietal lobes, with associated contraction of the adjacent extra-axial CSF spaces and significant decreases in tissue density in areas along the base of the brain, including the orbitofrontal cortex, with expansion of the basal extra-axial CSF spaces. We hypothesize that these unique structural alterations occurring during bed rest and possibly during spaceflight due to altered gravity gradients may provide explanations for the findings of the VIIP syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The pulsatile CSF motion caused by respiration, 34,35 body posture, 36 and venous pressure 37 should also be examined. Changes in intracranial pressure and venous return flow caused by respiration should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Methods In this prospective observational study, SctO 2 was measured in 85 awake volunteers serially positioned every 15 min, beginning with the supine position (SP) and followed by the beach chair, supine, and lateral decubitus positions. Cerebral tissue oxygen saturation was also measured supine and in either the BCP or the LDP in 195 patients (according to surgical preference) undergoing elective arthroscopic shoulder surgery.…”
Section: Introductionmentioning
confidence: 99%